2012
DOI: 10.1140/epjb/e2012-20675-4
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical imaging of elastic strain-controlled magnetization reorientation

Abstract: We study the validity and limitations of a macrospin model to describe the voltage-controlled manipulation of ferromagnetic magnetization in nickel thin film/piezoelectric actuator hybrid structures. To this end, we correlate simultaneously measured spatially resolved magneto-optical Kerr effect imaging and integral magnetotransport measurements at room temperature. Our results show that a macrospin approach is adequate to model the magnetoresistance as a function of the voltage applied to the hybrid, except f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
(52 reference statements)
0
9
1
Order By: Relevance
“…[4][5][6][7][8][9][10] It has been shown that a robust electric field control of magnetism can be realized by using extrinsic multiferroic hybrid structures consisting of ferroelectric and ferromagnetic materials. [11][12][13][14][15] In these systems, the extrinsic magnetoelectric effects rely on either electric field effects 16 using carrier mediated ferromagnets, 17 or employing exchange coupling effects between antiferromagnetic, ferroelectric and ferromagnetic compounds. 18,19 Moreover, from the beginning the elastic coupling at the interface between ferromagnetic and ferroelectric materials has been exploited to realize a robust electric field control of the magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] It has been shown that a robust electric field control of magnetism can be realized by using extrinsic multiferroic hybrid structures consisting of ferroelectric and ferromagnetic materials. [11][12][13][14][15] In these systems, the extrinsic magnetoelectric effects rely on either electric field effects 16 using carrier mediated ferromagnets, 17 or employing exchange coupling effects between antiferromagnetic, ferroelectric and ferromagnetic compounds. 18,19 Moreover, from the beginning the elastic coupling at the interface between ferromagnetic and ferroelectric materials has been exploited to realize a robust electric field control of the magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Strain driven magnetization reversal of a macroscopic Ni disc on a piezoelectric actuator indicate that the mechanisms for strain driven and field driven magnetization reversal are similar, 20 with short axis magnetization reversal dominated by coherent rotation and easy axis reversal showing domain formation close to the switching strain. In contrast, strain-driven magnetization reorientation in highly magnetostrictive microstructures of thin film FeGa (Ref.…”
Section: Measurementsmentioning
confidence: 96%
“…However the application of its antiferromagnetism, instead of ferromagnetism, is still hard to accomplish. Furthermore, the coupling between ferromagnetic metal and ferroelectric oxide, named artificial multiferroics, has currently attracted much attention and actually provides more possibilities for functionality design [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The coupling between ferromagnetism and ferroelectricity is mediated by the magneto-elastic effect through the reversible electric-field-controlled strain variation [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the coupling between ferromagnetic metal and ferroelectric oxide, named artificial multiferroics, has currently attracted much attention and actually provides more possibilities for functionality design [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The coupling between ferromagnetism and ferroelectricity is mediated by the magneto-elastic effect through the reversible electric-field-controlled strain variation [22][23][24][25][26]. The ferroelectric materials of BaTiO 3 (BTO) [32][33][34][35] and Pb(Zr x Ti x 1− )O 3 (PZT) [26][27][28][29][30][31] have been widely used in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation